The extracranial facial nerve: high resolution three-dimensional Fourier transform MR imaging. - McGhee, R B; Chakeres, D W; Schmalbrock, P; Brogan, M A; Negulesco, J A (American Journal of Neuroradiology, 1993)
PURPOSE To investigate the use of high-resolution three-dimensional Fourier transform gradient-echo MR in evaluation of the extracranial facial nerve.METHODS Nine normal subjects and one clinical patient were scanned. Several imaging parameters, including echo time, field-of-view, and the use of Gd-DTPA, were manipulated to determine the optimal technique. Adequate results were obtained in less than 7 minutes acquisition time using a T1-weighted (50/5.3) gradient-echo technique, with a 30 degree flip angle, a 12-cm field of view, 128 x 256 matrix, and 28 or 60 1.0-mm-thick contiguous sections.RESULTS Gd-DTPA administration was not found useful in identifying the normal extracranial facial nerve. The proximal extracranial facial nerve was seen as a branching low signal intensity tubular structure on 10 to 20 contiguous images in all five volunteers in which this optimal technique was employed. Postprocessing of the images to produce curved oblique planar reconstructed images was useful to display long segments of the facial nerve on a single image.CONCLUSION Our experience with high resolution three-dimensional Fourier transform MR imaging indicates that it can consistently demonstrate the intraparotid facial nerve on multiple contiguous images.